Letter to Jane Tolmach from Alvin C. Weingand - Alvin C. Weingand:::::: (1966)
A letter from California State Senator Alvin C. Weingand informs Mrs. Jane Tolmach of her appointment to the Democratic State Central Committee and expresses confidence in her service. He notes that the Committee will meet at the State Capitol on August 14 following the State Convention and encourages her to attend both events. A proxy form is enclosed for her to complete if she is unable to be present.